The Effects of Technologyb Readiness and Technology Acceptance toward Citizens Participation in Bandung Smart City Project - Lubis, Febryansyah Aminullah; Mirzanti, Isti Raafaldini (Journal of Business and Management, 2016)
Abstract.Smart city is a world phenomenon that also affected Bandung. Bandung government wants to apply smart city to Bandung which leads to Bandung smart city project. The project main focus is the Smart government. Citizens could actively participate in Bandung smart city project by using social media for reporting city problems. This study goal to know the effects of technology readiness and technology acceptance toward citizens’ participation. The research model based on two theories, technology readiness index and technology acceptance model. The data for this study collected from 400 citizens of Bandung. The results of the study showed that four constructs of technology readiness significantly affected perceived ease of use while only two constructs of technology readiness significantly affected perceived usefulness. Both perceived ease of use and perceived usefulness significantly affected intention to use. The result of this study suggests that to increase citizens’ participation towards Bandung smart city project, the government needs to do direct socialization to reach more elements of citizens.Keywords: Technology Readiness, Technology Acceptance Model, Smart City, Bandung Juara